Assessing Stakeholder Perceptions in Participatory Infrastructure Upgrades - a Case Study of Project Silvertown in Cape Town - Kumbirai, Shamiso (Department of Civil Engineering, 2019)
This study articulates the perceptions and expectations stakeholders involved in sanitation infrastructure projects in informal settlements have to determine the implications their contrasting views have towards strengthening participatory processes. It involves the critical identification of stakeholder groups and their perceptions of the roles and responsibilities that the identified groups play. The investigation was conducted using the single case study of Project Silvertown, the project that led to the controversial 2010 “toilet war saga” in Cape Town’s Khayelitsha Township. Documentary resources on the case study were used to gather secondary data on stakeholder groups and analysed using Critical Systems Heuristics, a systems thinking-based framework. The key findings in this study were that • there were disjunctions within the spheres of government relating to policy interpretations; • there were known disjunctions on project vision and outcomes between stakeholder groups that were not resolved; • there were disjunctions relating to stakeholder expectations of community participation and decision making • there was poor capacitation of community members in the participatory process • there was illegitimate representation of the residents by community leaders Findings of the conflicts between stakeholders in a given system can contribute towards identifying what stakeholder assumptions ought to be considered and built into planning public infrastructure projects to reduce participatory project failures